Addiction as a disorder of belief - Levy, N (Springer Netherlands, 2014)
Addiction is almost universally held to be characterized by a loss of control over drug-seeking and consuming behavior. But the actions of addicts, even of those who seem to want to abstain from drugs, seem to be guided by reasons. In this paper, I argue that we can explain this fact, consistent with continuing to maintain that addiction involves a loss of control, by understanding addiction as involving an oscillation between conflicting judgments. I argue that the dysfunction of the mesolimbic dopamine system that typifies addictions causes the generation of a mismatch between the top-down model of the world that reflects the judgment that the addict ought to refrain from drugs, and bottom-up input caused by cues predictive of drug availability. This constitutes a powerful pressure toward revising the judgment and thereby attenuating the prediction error. But the new model is not stable, and shifts under the pressure of bottom-up inputs in different contexts; hence the oscillation of all-things-considered judgment. Evidence from social psychology is adduced, to suggest that a similar process may be involved in ordinary cases of weakness of will.